Autonomous learning, self-regulated learning, and Arabic reading comprehension: A quasi-experimental study - Arifin, Shokhibul; Degeng, I Nyoman Sudana; Setyosari, Punaji; Ulfa, Saida (Universitas Jambi, Indonesia, 2026)
This study examined how instructional strategy and self-regulated learning (SRL) relate to students’ Arabic reading comprehension. A quasi-experimental 2 × 2 factorial design was used with 120 students enrolled in Arabic courses at Universitas Muhammadiyah Surabaya. Two intact classes completed autonomous-learning activities, while two other classes followed cooperative-learning activities. Students were grouped into high- and low-SRL categories based on questionnaire scores. Data were collected through pre-tests and post-tests and analyzed using descriptive statistics, an independent-samples t-test, and two-way ANOVA. The pre-test results showed no significant difference between the two instructional groups. Post-test results indicated significant effects of learning strategy, SRL level, and their interaction. These findings suggest that the suitability of autonomous and cooperative reading activities may differ according to students’ SRL levels. Because intact classes were used, the results should be interpreted cautiously.